Дослідження впливу похідного пептидамідобензофенону на поведінку кіндлінгових тварин = Research of behavior of kindling animals under conditions of derivative peptideaminobenzophenones - Pogorila, I. V.; Tregub, T. V. (Journal of Education, Health and Sport, 2015)
Pogorila I. V., Tregub T. V. Дослідження впливу похідного пептидамідобензофенону на поведінку кіндлінгових тварин = Research of behavior of kindling animals under conditions of derivative peptideaminobenzophenones. Journal of Education, Health and Sport. 2015;5(9):726-738. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35719 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A726-738 https://pbn.nauka.gov.pl/works/685040 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.08.2015. Revised 05.09.2015. Accepted: 29.09.2015. УДК 616.853-092.9:599.323.4]-085.213 ДОСЛІДЖЕННЯ ВПЛИВУ ПОХІДНОГО ПЕПТИДАМІДОБЕНЗОФЕНОНУ НА ПОВЕДІНКУ КІНДЛІНГОВИХ ТВАРИН RESEARCH OF BEHAVIOR OF KINDLING ANIMALS UNDER CONDITIONS OF DERIVATIVE PEPTIDEAMINOBENZOPHENONES І. В. Погоріла, Т. В Трегуб I. V. Pogorila, T. V. Tregub Одеський національний медичний університет, м. Одеса, Україна Odessa National Medical University, Odessa, Ukraine Summary In corazol-induced kindling animals (30,0 mg/kg, i.p. 21 injections) it was revealed reduction of the variability of swimming behavior, worsening of avoidance behavior from swimming-pool, increasing of aggression. Derivative of peptideamidobenzophenones (PABPh) at 0,15 mg/kg induced the increasing of the variability of swimming behavior upto 50,0 %, in the same time the drug of comparing diazepame (0,05 mg/kg) – only on 20,5 %. After administration of derivative of PABPh (0,15 mg/kg) one can saw the reduction of avoidance threshold of the kindling rats in 3 times, while under the action of diazepame (0,05 mg/kg) – on 19,1 %. Derivative of PABPh in the dosages of 0,15 and 1,5 mg/kg increased the fighting threshold by 70,0 % and in 2,28 times fold correspondently, diazepame (0,05 mg/kg) increased the threshold of fighting’s in pairs of kindled rats by 40,0 %, comparatively to untreated animals. Significant derivative of PABPh induced effects maintained during 2,5 h, while effects of diazepame disappeared in 1,5 h from the moment of drugs administration. Key words: derivative of peptideamidobenzophenones, diazepame, сorazol kindling, swimming, aggressive behaviors. Резюме В умовах кіндлінгу, індукованого застосуванням коразолу (30,0 мг/кг, 21 ін’єкція), знижувалася варіабельність плавання, утруднялося уникнення тварин з басейну, зростала їх агресивність. Похідне пептидамідобензофенону (ПАБФ) дозою15 мг/кг підвищувало варіабельність плавання кідлінгових щурів до 50,0 %, тоді як препарат порівняння діазепам (0,05 мг/кг) – тільки на 20,5 %. При введенні похідного ПАБФ (0,15 мг/кг) знижувався поріг уникнення з басейну кідлінгових щурів у ,0 рази, а під впливом діазепаму (0,05 мг/кг) – на 19,1 %. Похідне ПАБФ дозами 0,15 і 1,5 мг/кг збільшувало поріг розвитку бійок в парах кіндлінгових щурів відповідно на 70,0 % і в 2,3 рази, а діазепам (0,05 мг/кг) – на 40,0 % порівняно з групою кіндлінгових щурів без лікування. Виразна дія похідного ПАБФ на поведінку тварин спостерігалася і через 2,5 год з моменту його введення, тоді як ефекти діазепаму відзначалися тільки протягом 1,5 год. Ключові слова: похідне пептидамідобензофенону, діазепам, коразоловий кіндлінг, плавальна, агресивна поведінка. Резюме ИССЛЕДОВАНИЕ ВЛИЯНИЯ ПРОИЗВОДНОГО ПЕПТИДАМИДОБЕНЗОФЕНОНА НА ПОВЕДЕНИЕ КИНДЛИНГОВЫХ ЖИВОТНЫХ. В условиях киндлинга, индуцированного применением коразола (30,0 мг/кг, 21 инъекция), снижается вариабельность плавания, затрудняется избегание животных из бассейна, возрастает их агрессивность. Производное пептидамидобензофенона (ПАБФ) в дозе 0,15 мг/кг повышало вариабельность плавания киндлинговых крыс до 50,0 %, в то время как препарат сравнения диазепам (0,05 мг/кг) – только на 20,5 %. При введении производного ПАБФ (0,15 мг/кг) снижался порог избегания из бассейна киндлинговых крыс в 3,0 раза, а под влиянием диазепама ( 0,05 мг/кг) – на 19,1 %. Производное ПАБФ в дозах 0,15 и 1,5 мг/кг увеличивало порог развития драк в парах киндлинговых крыс соответственно на 70,0 % и в 2,3 раза, а диазепам (0,05 мг/кг) – на 40,0 % в сравнении с группой киндлинговых крыс без лечения. Выраженное действие производного ПАБФ на поведение животных наблюдалось и через 2,5 ч с момента его введения, в то время как эффекты диазепама отмечались только на протяжении 1,5 ч. Ключевые слова: производное пептидамидобензофенона, диазепам, коразоловый киндлинг, плавательное, агрессивное поведение.